Predation evaluation of the green lacewing, Chrysopa pallens on the pink tea mite pest, Acaphylla theae (Watt) (Acarina: Eriophyidae) - Wang, Qian; Zhang, Meng; Guo, Qiuyu; Wu, Chenxin; Sun, Liang (Frontiers in Physiology, 2023)
A better understanding of predator-prey interactions is crucial for the development of biological control strategies. The green lacewing, Chrysopa pallens, is a well-known generalist predator and reportedly functions as one of the most important biological control agents of insect pests. However, information regarding C. pallens’ predation on tea plant pests, particularly notorious tea mites, remains largely unknown. In this study, we focused on the predator-prey relationship between C. pallens and an important tea mite pest, Acaphylla theae. We designed species-specific primers for the detection of A. theae DNA and established a PCR-based DNA gut content analysis assay. These results demonstrated that the primers were A. theae-specific and suitable for its molecular identification. The laboratory feeding experiment showed that the detectability success (DS50) of A. theae DNA remaining in C. pallens’ guts was 2.9 h. We then performed a molecular detection of field predation, and achieved a 23.53% positive detection rate of A. theae DNA in the guts of field-collected C. pallens. This, for the first time, provides direct evidence that C. pallens can prey on A. theae in tea plantations. Finally, we tested the prey preference and estimated the predation ability of C. pallens on different developmental stages of A. theae. The results revealed that C. pallens had no significant preference for different developmental stages of A. theae. The functional responses of C. pallens’ predation on different densities of A. theae at different developmental stages followed a Type II Holling model. The initial attack rate (a′) ranged from 0.735 to 0.858 and the handling time (Th) was approximately 0.01. This study is the first to demonstrate the trophic interactions between C. pallens and A. theae and provides evidence for the development of biological control strategies against A. theae using C. pallens as a candidate predator.